Improved repair of dermal wounds in mice lacking microRNA‐155. Issue 6 (17th March 2014) - van Solingen, Coen; Araldi, Elisa; Chamorro‐Jorganes, Aranzazu; Fernández‐Hernando, Carlos; Suárez, Yajaira
Abstract Wound healing is a well‐regulated but complex process that involves haemostasis, inflammation, proliferation and maturation. Recent reports suggest that microRNAs (miRs) play important roles in dermal wound healing. In fact, miR deregulation has been linked with impaired wound repair. miR‐155 has been shown to be induced by inflammatory mediators and plays a central regulatory role in immune responses. We have investigated the potential role of miR‐155 in wound healing. By creating punch wounds in the skin of mice, we found an increased expression of miR‐155 in wound tissue when compared with healthy skin. Interestingly, analysis of wounds of mice lacking the expression of miR‐155 (miR‐155−/−) revealed an increased wound closure when compared with wild‐type animals. Also, the accelerated wound closing correlated with elevated numbers of macrophages in wounded tissue. Gene expression analysis of wounds tissue and macrophages isolated from miR‐155−/− mice that were treated with interleukin‐4 demonstrated an increased expression of miR‐155 targets (BCL6, RhoA and SHIP1) as well as, the finding in inflammatory zone‐1 (FIZZ1) gene, when compared with WT mice. Moreover, the up‐regulated levels of FIZZ1 in the wound tissue of miR‐155−/− mice correlated with an increased deposition of type‐1 collagens, a phenomenon known to be beneficial in wound closure. Our data indicate that the absence of miR‐155 has beneficial effects in the wound healing process.